Dietary Supplementation with Saccharomyces cerevisiae, Clostridium butyricum and Their Combination Ameliorate Rumen Fermentation and Growth Performance of Heat-Stressed Goats - Cai, Liyuan (Animals (Basel), 2021)
SIMPLE SUMMARY: Heat stress commonly happens to goats raised in the Jianghuai region of China during the summer and inevitably contributes to a loss of animal production. Dietary supplementation with probiotics is one of the practical approaches to improve animal production. By dietary supplementation with Saccharomyces cerevisiae, Clostridium butyricum, and their combination to the heat-stressed goats, the present study showed these probiotics effectively alleviate heat stress by improving the rumen fermentation function and growth performance. Therefore, this study provides a reference for the application of these two probiotics in ruminant production during heat stress. ABSTRACT: This study aimed to evaluate the effects of Saccharomyces cerevisiae, and their combination on rumen fermentation and growth performance of heat-stressed goats. Twelve heat-stressed goats (20.21 ± 2.30 kg) were divided equally into four groups: control group (CG, fed the basal diet, Saccharomyces cerevisiae supplemented group (SC, 0.60% Saccharomyces cerevisiae added to the basal diet), Clostridium butyricum supplemented group (CB, 0.05% Clostridium butyricum added to the basal diet), and their combination supplemented group (COM 0.60% Saccharomyces cerevisiae and 0.05% Clostridium butyricum added to the basal diet) and were assigned to a 4 × 3 incomplete Latin square design. The rumen fluid and feces were collected for fermentation parameters and feed digestibility analysis, and animal growth performance was also assessed during all the experiment periods. The results showed that rumen pH, rumen cellulolytic enzymes (avicelase, CMCaes, cellobiase, and xylanase) activities, and the concentrations of rumen total volatile fatty acid (TVFA), acetic acid, and propionic acid were significantly increased with Saccharomyces cerevisiae, Clostridium butyricum, and their combination supplementation (p < 0.05). Besides, the dry matter intake (DMI), average daily gain (ADG), and the digestibility of dry matter (DM), neutral detergent fiber (NDF), and acidic detergent fiber (ADF) were significantly increased (p < 0.05) with supplemented these probiotics. However, the ammonia nitrogen (NH(3)-N) concentration only significantly increased in CB and A/P ratio (acetic acid to propionic acid ratio) only significantly increased in SC and CB. These results indicated that the supplementation with these probiotics could ameliorate rumen fermentation and growth performance of heat-stressed goats.